Adherence to Southern European Atlantic Diet and physical fitness on the atherogenic index of plasma in adolescents - César Agostinis-Sobrinho; Arieli Fernandes Dias; Caroline Brand; Sigute Norkiene; Sandra Abreu; Adroaldo Cezar Araujo Gaya; Anelise Reis Gaya; Luís Lopes; Carla Moreira; Jorge Mota; Rute Santos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: We sought (i) to evaluate the associations of cardiorespiratory fitness (CRF), muscular fitness (MF) and Southern European Atlantic Diet (SEADiet) with atherogenic index of plasma (AIP) and (ii) to investigate de combined association of MF, CRF and SEADiet on AIP in adolescents. A cross-sectional school-based study was conducted on 493 adolescents (285 girls and 208 boys) aged 15-18 years, from the Portuguese Azorean Archipelago. CRF was measured by shuttle run test and MF by curl up and push up tests. Adherence to SEADiet was assessed with a semi-quantitative food frequency questionnaire (FFQ). The AIP was estimated as log (TG/HDL-C). Measures of pubertal stage and socioeconomic status were assessed. Linear regression showed a significant inverse association between MF (standardized β = -0.165; p < 0.001), CRF (standardized β = -0.081; p < 0.030) and SEADiet (standardized β = -0.081; p < 0.045) with AIP, after adjustments for age, sex, pubertal stage and parental education. Furthermore, participants classified with an optimal as well as those with low adherence to a SEADiet but with LowMF/LowCRF had on average the highest AIP (F(7.482) = 3.270; p = 0.002). Moreover, optimal SEADiet with HighMF/HighCRF group showed the lowest AIP when compared with those with low adherence to a SEADiet with HighMF/HighCRF group (p = 0.03). AIP is inversely associated with MF, CRF and SEADiet. The low MF combined with a low CRF levels seems to overcome the potential healthy effect of having an optimal adherence to the SEADiet on AIP. However, an optimal adherence to SEADiet seems to improve the AIP in those adolescents with high fitness levels.